Actualization of Religious Moderation in Islamic Fatwas in Mainstream Online Media in Indonesia - Asa'ari; Nuzul Iskandar; Hainadri (Jurnal Penelitian, 2023)
This study is intended to explain the actualization of religious moderation in Islamic fatwas in mainstream media in Indonesia. This study uses a qualitative-descriptive approach, in the form of media text studies combined with field studies. The media that is used as the object of study is Republika online which is considered to be able to represent mainstream media that has an interest in Islamic issues. Data analysis uses the critical discourse analysis method developed by Teun A van Dijk. This study conveys that in general the contents of fatwas in Republika have actualized and supported the agenda of religious moderation in Indonesia, but when measured by each indicator, the contents of religious moderation tend to only appear in formal in national commitment aspect, tend to avoid diversity of insight because of the urge to always be moderate, and only convey the physical and manifest violence by disregarding that of non-physical and latent. Meanwhile, accommodative indicators of local culture tend to be overlooked in almost all fatwa content, even though many issues potentially can be linked to this. This study is limited to fatwas that contain state issues, while the content of religious moderation can be seen in a wider spectrum of issues. Therefore, this deficiency can be continued by future researchers. However, this study can contribute to providing a qualitative picture of the extent to which the mass media, especially the mainstream media, play a role in the agenda of religious moderation in Indonesia.